ENHANCING INDONESIAN SCIENCE TEACHER PERSPECTIVE OF AND BELIEF IN STEM THROUGH PROFESSIONAL DEVELOPMENT - Pramudya Dwi Aristya Putra; Nurul Fitriyah Sulaeman; Albertus Djoko Lesmono; Rif’ati Dina Handayani (Jurnal Pengajaran MIPA, 2022)
A perspective on STEM education drives the teachers' conceptual for developing a design material in STEM approach. Lack of understanding of STEM education is becoming a challenge to implement STEM approaches in the classroom for the teacher. The purpose of this study was to describe the science teachers' perspective on STEM educational approach after following the professional development in STEM education, which was conducted including in the theoretical of STEM education and implementation in the classroom. This study used a single case method that focused on changing a teacher's attitude on STEM education. The professional development was conducted in a relationship program with the Fulbright specialist in 20 hours for training in STEM education. The result described the interview process between the researcher and the teachers that there was a shift a teachers' perspective more integrated into STEM education. They believe that STEM education can be implemented in Indonesia to address the real-world problems which students experience.